How Nestle Succeed in the Food Industry: A Consumer Perspective - Kee, Daisy Mui Hung; Syakirah, Nur Hannis; Najihah, Nurun; Aliya, Nur Anis; Sikumbang, Nur Zahirah (International Journal of Tourism and Hospitality in Asia Pasific, 2021)
The purpose of this study is to analyze consumer perception of how Nestle succeeds in the food industry. The study employed a quantitative research approach, and an online survey was carried out. Data were collected from 121 Nestle consumers in Malaysia. The results show that Nestle's success factor is from the provision of good products at a reasonable price and marketing strategies that Nestle has developed to be the main driver of the growth, which contribute to the organizational success. Discussion and recommendations are presented.